Liver transplant outcomes using ideal donation after circulatory death livers are superior to using older donation after brain death donor livers. Issue 9 (September 2016) - Scalea, Joseph R.; Redfield, Robert R.; Foley, David P.
Abstract : Multiple reports have demonstrated that liver transplantation following donation after circulatory death (DCD) is associated with poorer outcomes when compared with liver transplantation from donation after brain death (DBD) donors. We hypothesized that carefully selected, underutilized DCD livers recovered from younger donors have excellent outcomes. We performed a retrospective study of the United Network for Organ Sharing database to determine graft survivals for patients who received liver transplants from DBD donors of age ≥ 60 years, DBD donors < 60 years, and DCD donors < 50 years of age. Between January 2002 and December 2014, 52, 271 liver transplants were performed in the United States. Of these, 41, 181 (78.8%) underwent transplantation with livers from DBD donors of age < 60 years, 8905 (17.0%) from DBD donors ≥ 60 years old, and 2195 (4.2%) livers from DCD donors < 50 years of age. DCD livers of age < 50 years with < 6 hours of cold ischemia time (CIT) had superior graft survival when compared with DBD livers ≥ age 60 years ( P  < 0.001). In 2014, there were 133 discarded DCD livers; of these, 111 (83.4%) were from donors < age 50 years old. Young DCD donor livers (age < 50 years old) with short CITs yield results better than that seen with DBD livers > 60 years old. Careful donor organ and recipient selection can lead to excellent results, despite previous reports suggesting otherwise. Increased acceptance of these DCD livers would lead to shorter wait list times and increased national liver transplant rates. Liver Transplantation 22 1197–1204 2016 AASLD